PENDIDIKAN TEKNOLOGI UNTUK PEREMPUAN - Hidayat, Andi Nurul (Musawa: Journal for Gender Studies, 2020)
Technology education is a right for everyone in this world. Therefore, there is no reason to discriminate against technological education especially for women in Indonesia. In the perspective of technology for women, there is a high desire to master technology to enable women to build meaningful interpretations and personal representations. In addition, technology is also useful as a rich and flexible learning tool for women, in this article it is targeted to discuss the importance of technology education and independence to women, especially independence in the family economy. Women who have broader knowledge and more competent economic skills will be more independent, stronger, and will be more successful in carrying out their roles and functions in the family, society, and national development. The level of compatibility between technological values ​​and norms with the values ​​or norms of its users will determine the pattern The use of this technology starts from the value of most of the goods and services of information and communication technology (ICT) which tends to be more masculine, which is one of the causes of the digital divide in technological women.